Teaching Note—An Ecological Conceptual Framework for Preparing Social Work Students for Practice With Refugee Populations. (3rd July 2022) - Hagues, Rachel; Cecil, David
ABSTRACT: Drawing from original and best practice research, this article proposes a model for teaching social work students how to practice with refugees using Bronfenbrenner's ecological model as a guide. Social workers globally must be prepared across the social work curriculum with best practice research and recommendations that keep pace with the largest refugee crisis the world has ever known. This article proposes a teaching framework based on empirical data, social work scholarship, and information on refugee needs and best practice approaches.